The Antioxidant Properties and Chemical Composition of Stachys inflata Benth Leaves Grown Wild in Lorestan Province - Hassan Ahmadvand; Sima Farajollahi *; Hamze Amiri; Ali Amiri (Herbal Medicines Journal, 2017)
Background and Aim: In recent years there has been an increasing interest in herbal medicines and natural antioxidant products to be used as medicines and food additives. The present research identified the various antioxidative activities of ethanol and methanol extracts, and chemical composition of Stachys inflate Benth leaves essential oil.